1996
DOI: 10.1002/art.1780390406
|View full text |Cite
|
Sign up to set email alerts
|

src‐related tyrosine kinases regulate transcriptional activation of the interstitial collagenase gene, MMP‐1, in interleukin‐1‐stimulated synovial fibroblasts

Abstract: Objective. To characterize tyrosine kinases that contribute to the transcription of interstitial collagenase.Methods. Four thousand six hundred fourteen basepairs of the rabbit collagenase promoter region were cloned and sequenced. Plasmids containing collagenase promoter fragments linked to the luciferase reporter gene were transiently transfected into primary rabbit synovial fibroblasts. Regulation of gene activation by inflammatory mediators and tyrosine kinase inhibitors was assessed. To identify specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
0
1

Year Published

1997
1997
2001
2001

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 33 publications
2
32
0
1
Order By: Relevance
“…Xu and Clark (1997) have indeed shown that PKC-ζ is activated in RCG and participates in the up-regulation of the MMP-1. Other authors (Sudbeck et al, 1994;Vincenti et al, 1996) and ourselves (Lambert et al, 1998) have also demonstrated that TPA-induced expression of MMP-1 is inhibited by tyrosine kinase inhibitors, suggesting that PKC may act upstream of Src in the upregulation of the MMPs by phorbol esters and CD, and possibly also in RCG.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Xu and Clark (1997) have indeed shown that PKC-ζ is activated in RCG and participates in the up-regulation of the MMP-1. Other authors (Sudbeck et al, 1994;Vincenti et al, 1996) and ourselves (Lambert et al, 1998) have also demonstrated that TPA-induced expression of MMP-1 is inhibited by tyrosine kinase inhibitors, suggesting that PKC may act upstream of Src in the upregulation of the MMPs by phorbol esters and CD, and possibly also in RCG.…”
Section: Discussionmentioning
confidence: 85%
“…In this context, it is worth noting that the transient expression of v-src induces MMP-1 expression in rabbit synovial fibroblasts (Vincenti et al, 1996). Furthermore, the genetic suppression of src in mice decreases bone degradation resulting in an osteopetrotic phenotype (Soriano et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of MMP-1, constituents of oxidatively modified lipoproteins that stimulate protein kinase C might link to the activator protein-1 (AP1)-mediated transcriptional regulation that plays a key role in controlling transcription of MMP-1. 31 Gelatinase-B, also known as 92-kD gelatinase, or MMP-9, may contribute importantly to instability of human atherosclerotic plaques. 8,32 The regulation of tran- …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, tyrosine kinase is another important mediator for the regulation of MMP-1 transcription (53)(54)(55). Tyrosine kinase can be classified into the receptor type and nonreceptor type; however, it is not clear which type of tyrosine kinase is involved in the signal transduction for the up-regulation of MMPs by MIF.…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosine kinase can be classified into the receptor type and nonreceptor type; however, it is not clear which type of tyrosine kinase is involved in the signal transduction for the up-regulation of MMPs by MIF. It was reported that transcriptional activation of MMP-1 by TPA and IL-1␤ was inhibited by herbimycin A, but not by tyrphostin A25, an epidermal growth factor receptor tyrosine kinase inhibitor (53). Herbimycin A exerts a selective inhibitory effect on src-related tyrosine kinase (56).…”
Section: Discussionmentioning
confidence: 99%